Competitive Strategy of Firms' Participation in the Global Value Chains and Labor Income Share. (7th December 2021) - Sun, Zhaoji; Tang, Danling; Li, Qing
Abstract : The division of labor in the global value chain (GVC) has reshaped the competitive advantage of enterprises participating in the international market and has a significant influence on the distribution of their factor income. Based on the perspective of market choice, this paper uses China's industrial enterprises' data, Customs Statistical Data on Import and Export, Word Input and Output Database (WIOD), and BACI database from 2000 to 2007 to analyze the effect of competitive strategy of a firm's GVC participation on its labor income share. Herein, the competition strategy is depicted by the quality and price of export goods. The empirical results show the following. (1) Quality competition has a larger effect on labor income share than price competition. High-quality and high-price or high-quality and low-price strategies tend to have a significant negative effect on labor income share, while low-quality and low-price and low-quality and high-price strategies have a positive effect. (2) The higher the target market GVC status, the lower the labor income share of exporting firms, and the target market GVC status amplifies that the high-quality and high-price strategies on firms' labor income share the negative effect of high-quality and low-price strategies on exporters' labor income share. (3) High-quality and low-price strategies have a significant negative effect on exporters' labor income share when competing with developing countries in developed country markets or with developed countries in developing country markets. However, the positive effect of low-quality and low-price strategies and low-quality and high-price strategies kept unchanged. The findings remain robust after controlling for endogeneity and accounting for the effects of firm heterogeneity, indicator measurement, and sample variation.